One journalist, two roles : what happens when journalists also work as media coordinators? - Tandoc, Edson C. (2015)
Individuals interacting with society possess multiple roles, and yet the study of journalistic role conceptions, based on the assumption that role conceptions influence journalistic outputs, has not addressed the idea that journalists possess multiple roles inside and outside the journalistic field. A peculiar arrangement in Missouri is the appointment of journalists to serve as media coordinators for the courts. Using a symbolic interactionism framework, we explore how media coordinators experience this duality of roles.